Production of mycelial biomass and lignocellulolytic enzymes of Pleurotus spp. in liquid culture medium (Research, Society and Development, 2021)
Pleurotus spp. are fungi capable of degrading lignocellulose material due to the excretion of enzymes with different industrial applications. This study aimed to investigate the influence of culture media on the production of mycelial biomass and the activity of laccase, cellulases, and xylanase of Pleurotus spp. Pleurotus citrinopileatus U16-23, P. djamor U16-20, U16-25, and U16-28, P. eryngii U16-30, P. ostreatus U16-22, and P. pulmonarius U16-21 were grown for 12 days at 28 ºC in malt extract medium (EM-20 g L-1), defined medium (MD glucose 10 g L-1 and yeast extract 2 g L-1), or in sugarcane bagasse (BC) medium equal to MD, but replacing glucose with bagasse (50 g L-1). The greatest growth occurred in the medium EM and P. djamor U16-25 was the strain that generated the greatest biomass (7.5 ± 0.1 g L-1). Most strains showed higher laccase activity in the MD medium and the greatests activities were P. djamor U16-25 (22243 ± 745 U L-1), and P. pulmonarius (20924 ± 46 U L-1). P. citrinopileatus and P. djamor U16-25 did not produce cellulases, but P. djamor U16-20 and P. eryngii produced the greatest cellulase activities in EM and MD media. All strains produced xylanase, and the highest activities were observed in the EM medium and P. djamor U16-28 (67154 ± 1597 U L-1) was the best producer. Pleurotus djamor U16-25 excelled as a producer of laccase and cellulase-free xylanase, revealing the potential for application in the paper and cellulose industry.